Penerapan Arsitektur Eko Organik Pada Resort Pantai Di Kabupaten Pacitan - Kurniawan, Muhammad Dicky; Istijanto, Suko; Wilfritz Soaduon Panjaitan, Tigor (Rifa'Institute, 2024)
The tourism industry and creative economy have had a very good impact on society's growth rate, but the arrival of the pandemic could